2019
DOI: 10.1159/000500483
|View full text |Cite
|
Sign up to set email alerts
|

Patients Who Attend Alone at a First Memory Consultation: Are They a Specific Population,or Is It an Instance of Confounding Bias?

Abstract: As commonly happens in epidemiological research, none of the reported studies were totally free of methodological problems. Studies have considered the influence of social relationships on dementia, but the mechanisms underlying these associations are not perfectly understood. We look at the possible impact of selection bias. For their first memory consultation, patients may come alone or accompanied by a relative. Our objective is to better understand the impact of this factor by retrospective follow-up of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…The association of elderly patients with poorer health with accompanied medical visits had already been demonstrated. 20 Our results were similar to those found by Koskas et al 8 , who, despite having evaluated patients in consultation at a memory clinic and, therefore, patients with higher risk for dementia, found lower MMSE scores in patients being accompanied. Patients searching for medical assistance in tertiary health care present more severe illnesses, more co-morbidities and consequently more vulnerability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association of elderly patients with poorer health with accompanied medical visits had already been demonstrated. 20 Our results were similar to those found by Koskas et al 8 , who, despite having evaluated patients in consultation at a memory clinic and, therefore, patients with higher risk for dementia, found lower MMSE scores in patients being accompanied. Patients searching for medical assistance in tertiary health care present more severe illnesses, more co-morbidities and consequently more vulnerability.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a companion has been less studied as a predictor of cognitive impairment in elderly patients. A study evaluating the presence of a companion in a memory clinic found reduced scores in the Mini-Mental State Examination (MMSE) among those with an accompanying person 8. The estimate of geriatric patients accompanied during their primary care medical visits ranges from 20% to 50% 9,10.…”
mentioning
confidence: 99%
See 1 more Smart Citation